2013
DOI: 10.1021/jp408745h
|View full text |Cite
|
Sign up to set email alerts
|

Radical Product Yields from the Ozonolysis of Short Chain Alkenes under Atmospheric Boundary Layer Conditions

Abstract: The gas-phase reaction of ozone with unsaturated volatile organic compounds (VOCs), alkenes, is an important source of the critical atmospheric oxidant OH, especially at night when other photolytic radical initiation routes cannot occur. Alkene ozonolysis is also known to directly form HO2 radicals, which may be readily converted to OH through reaction with NO, but whose formation is poorly understood. We report a study of the radical (OH, HO2, and RO2) production from a series of small alkenes (propene, 1-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 79 publications
2
48
1
Order By: Relevance
“…Here, L accounts for the sum of any other chemical loss processes for SCIs in the chamber, after correction for dilution, and neglecting other (non-alkene) chemical sinks for O 3 , such as reaction with HO 2 (also produced directly during alkene ozonolysis; Alam et al, 2013;Malkin et al, 2010), which was indicated through model calculations to account for < 0.5 % of ozone loss under all the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, L accounts for the sum of any other chemical loss processes for SCIs in the chamber, after correction for dilution, and neglecting other (non-alkene) chemical sinks for O 3 , such as reaction with HO 2 (also produced directly during alkene ozonolysis; Alam et al, 2013;Malkin et al, 2010), which was indicated through model calculations to account for < 0.5 % of ozone loss under all the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified the hydroperoxide rearrangement as dominant for SCIs with a syn configuration, determining their overall unimolecular decomposition rate (Niki et al, 1987;Rickard et al, 1999;Martinez and Herron, 1987;Johnson and Marston, 2008). This route has been shown to be a substantial non-photolytic source of atmospheric oxidants (Niki et al, 1987;Alam et al, 2013). CIs formed in the anti configuration are thought to primarily undergo rearrangement and possibly decomposition via a dioxirane intermediate ("the acid/ester channel"), producing a range of daughter products and contributing to the observed overall HO x radical yield (Johnson and Marston, 2008;Alam et al, 2013).…”
Section: Stabilised Criegee Intermediate Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gas-phase reaction of O3 with unsaturated VOCs involves electrophilic addition of O3 on >C=C< followed by unimolecular decomposition of the 1,2,3-trioxolane adduct (Alam et al, 2013). Therefore, the reactivity of unsaturated esters toward O3 should reflect the electronic density at the C=C double bond.…”
Section: O 3 Reaction With Unsaturated Estersmentioning
confidence: 99%
“…Also, tetramethyl ethylene consistently gave amongst the highest OH yields, in line with the model, because every carbonyl oxide can undergo the 1,4‐hydrogen shift. It should be noted that ethylene ozonation also generates OH radicals in the gas phase, although an alkenyl peroxide cannot form this way—obviously, different mechanisms can operate …”
Section: Atmospheric Chemistrymentioning
confidence: 99%